2019
DOI: 10.1093/auk/ukz019
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of structural color across molts: The effects of environmental conditions and stress on feather ultraviolet reflectance

Abstract: DEDICATIONThis work is dedicated to the jays, who captured my heart from the start, and who will hopefully continue to capture hearts for decades to come.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 100 publications
1
2
0
Order By: Relevance
“…Revealing these mechanisms would help us to understand the information conveyed by these traits and their temporal variation. In white plumage areas, studies have described within-individual, between-moult colour changes (see below), similar to those detected for other structural colours (UV-blue: Delhey et al 2006, Windsor et al 2019yellow: del Val et al 2010). In male Pied Flycatchers Ficedula hypoleuca, J€ arvist€ o et al (2016) found that wing patch UV reflectance was repeatable between two reproductive seasons and it increased if the male grew a larger wing-patch.…”
supporting
confidence: 59%
“…Revealing these mechanisms would help us to understand the information conveyed by these traits and their temporal variation. In white plumage areas, studies have described within-individual, between-moult colour changes (see below), similar to those detected for other structural colours (UV-blue: Delhey et al 2006, Windsor et al 2019yellow: del Val et al 2010). In male Pied Flycatchers Ficedula hypoleuca, J€ arvist€ o et al (2016) found that wing patch UV reflectance was repeatable between two reproductive seasons and it increased if the male grew a larger wing-patch.…”
supporting
confidence: 59%
“…Previous studies have shown great differences in the consistency of sexual traits in wild populations, depending, among others, on the ornament measured and the sex of individuals (see Chaine & Lyon 2015, Windsor et al . 2019). Several authors have, however, shown consistent differences among individuals in spite of intra‐individual ornament dynamism (Pérez‐Rodríguez 2008, Chaine & Lyon 2015, Montoya et al .…”
Section: Discussionmentioning
confidence: 99%
“…Studying the consistency of sexual traits across moults is essential for quantifying their phenotypic variation and to understand whether sexually selected traits can be honest signals of intrinsic, long-term individual quality. Previous studies have shown great differences in the consistency of sexual traits in wild populations, depending, among others, on the ornament measured and the sex of individuals (see Chaine & Lyon 2015, Windsor et al 2019. Several authors have, however, shown consistent differences among individuals in spite of intra-individual ornament dynamism (Pérez-Rodríguez 2008, Chaine & Lyon 2015, Montoya et al 2018.…”
Section: Consistency In the Size Of The White Wing Patchmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted July 10, 2023. ; https://doi.org/10.1101/2023.07.10.546769 doi: bioRxiv preprint (Brotons & Broggi, 2003). In Florida scrub-jays, adults manipulated with supplemental corticosterone had reduced chroma in their plumage (Windsor et al, 2019) while juveniles with artificially reduced plumage reflectance lost more dominance interactions (Tringali & Bowman, 2012), indicating complex interactions between physiology, phenotype, and behaviour. Future work involving experimental manipulations and controls on oxidative status may elucidate the relationships between morphological development, body condition, and prospecting efforts, and how these variables ultimately shape lifetime fitness.…”
Section: Discussionmentioning
confidence: 99%